Pastorale interaksie met vroue - gesien vanuit die beelde wat vir God gebruik word - Dreyer, Yolanda (Hervormde teologiese studies, 1998)
Pastoral care and counseling with women: God-images and theidentity of women. The focus of this article is on women in the pastoral care situation. Rather than the revolutionary approach of liberation theology, a choice is made here for a process of conscientisation. Consciousness should be raised concerning the harm that has come to women on account of the dominant male perspective. A correlaion is drawn between a conception of Scripture, God-images (King/Lord, Father, Friend, Mother) and the identity of women. The article concludes with an orientation of church and society within a postmodern paradigm toward an authentic life for women before God.